WDR5 is a prognostic biomarker of brain metastasis from non-small cell lung cancer - Li, Zheng; Liang, Nan; Wang, Na; Jia, Yan; Tian, Cui (Frontiers in Oncology, 2022)
Background Lung cancer (LC) is the most frequent caner type and causes the most cancer-related death. Brain metastases (BM) are the deadliest complications of lung cancer, and the prognostic biomarkers of BM are urgently needed. Materials and Methods In our study, we established an inception cohort including 122 patients with asynchronous BM from NSCLC, and further selected 70 patients who received radical surgery, which compromised the validation cohort. With immunohistochemistry, we investigated the expression of WDR5 in the cohort. By chi-square method, the correlations between WDR5 and clinicopathological factors were analyzed. The prognostic indicators were analyzed with the univariate analysis, and independent prognostic factors were identified by multivariate analysis with Cox-regression model. Results WDR5 is frequently expressed in the cytoplasm of BM from NSCLC. Patients with low or high expression of WDR5 account for 60% and 40% respectively. High expression of WDR5 indicates poor prognosis of BM from NSCLC (P=0.001). In addition to WDR5, KPS is also a prognostic factor of BM, and high KPS predicts favorable prognosis (P=0.006). WDR5 is an independent prognostic biomarker for poor prognosis of BM from NSCLC, with the cancer-related odds as 2.48. Conclusions High expression of WDR5 can predict the poor prognosis of BM, and WDR5 is an independent prognostic biomarker of BM from NSCLC. Patients with WDR5 overexpression are more high-risk to suffer BM-related death and should receive stricter post-operational supervision.